Penerapan E-LKPD dalam Upaya Pemahaman Keterampilan Berpikir Kreatif pada Pembelajaran IPA Materi Bioteknologi - Yuly Budiasih; Nur Rohmatul Aini (Al Jahiz: Journal of Biology Education Research, 2022)
E-LKPD is an electronic-based Student Worksheet. The application of E-LKPD is intended to develop learning materials in a digital and modern direction. This study aims to describe the importance of implementing E-LKPD in an effort to understand creative thinking skills in science learning, especially biotechnology materials. The study was carried out using a questionnaire distribution technique to 40 science teachers in all SMPNs in Bandar Lampung. The data analysis technique uses the percentage of data display / data presentation. The results showed that 59.375% used conventional LKPD, 60.625% applied ordinary E-LKPD, and 53.75% teachers applied audio-visual-based E-LKPD. Thus, the importance of implementing E-LKPD in an effort to understand students' creative thinking skills in science learning.